Effect of dietary graded levels of astaxanthin krill oil and high protein krill meal on the growth performance and stress resistance of post larval Litopenaeus vannamei under hyper‐intensive nursery culture. (8th November 2020) - Nunes, Alberto Jorge Pinto; Soares, Artur Nepomuceno; Sabry‐Neto, Hassan; Burri, Lena
Abstract: This study evaluated the effect of graded dietary levels of astaxanthin krill oil (AKO) and high protein krill meal (HPK) on the growth performance and stress resistance of postlarval (PL) Litopenaeus vannamei . Shrimp of 3.6–2.5 mg body weight (BW) were stocked in outdoor and indoor tanks at 2, 371–2, 504 PLs m −3, respectively. Diets contained 10.0, 30.0 and 50.0 g/kg AKO (outdoor) and 30.0, 50.0 and 70.0 g/kg AKO with 80.0 g/kg HPK (indoor). After 52 and 41 days of nursery in outdoor and indoor tanks, no statistical effect from the inclusion of AKO and AKO with HPK was observed on final mean survival (84.0%–91.8%), gained yield (1, 568–1, 611 g/m 3 ), daily growth (14.2–14.2 mg/day) and feed conversion ratio (1.70–0.89), respectively. However, final shrimp BW was significantly improved with 50.0 g/kg AKO (775 mg) and 30.0 g/kg AKO with 80.0 g/kg HPK (629 mg), respectively, compared with control groups (711 and 567 mg). Resistance to osmotic and thermal stress was significantly increased with 10.0 g/kg AKO. Enhancement in growth performance and resistance may be related to a higher supply of dietary EPA, DHA and astaxanthin resulting from the inclusion of AKO and HPK.